Development and Psychometric Evaluation of the HIV-Related Stigma in Health Facilities (HIV-SHF) Scale - Janet Alexis A. De los Santos (Journal of Health Science and Medical Research (JHSMR), 2023)
Objective: The literature presents a variety of Human Immunodeficiency Virus (HIV) stigma scales focused on the self, social aspects, and health worker issues. Scarcity was noted on instruments developed to assess HIV-related stigma in health facilities. This paper aims to present the rigors in designing and developing a psychometrically reliable and valid scale to assess HIV-related stigma in health facilities. Material and Methods: A sequential exploratory mixed method design was utilized following a Qual-Quan approach. Key informant interviews were used to gather first-hand experience of stigma in health facilities among key populations and persons living with HIV. Thematic analysis was utilized to analyze the narratives and pick out statements for item generation in the scale. The quantitative phase was done through item and scale validation, exploratory factor analysis, and reliability assessment using Cronbach’s alpha. Results: Two factors were extracted which were categorized as (1) Facility Structure and Protocol, and (2) Health Personnel. The scale has very high internal consistency as per Cronbach’s alpha value of 0.91, suggestive of its high reliability in measuring HIV-related stigma in health facilities. Conclusion: The scale may be utilized by health facilities to assess and evaluate their health service provision, particularly on their client’s perception of health facility-related stigma.